Influence of environmental factors on the accumulation volatile compounds in Salvia officinalis essential oil and hydrolate - Aćimović Milica; Stanković-Jeremić Jovana; Cvetković Mirjana; Todosijević Marina; Vujisić Ljubodrag; Sikora Vladimir; Lončar Biljana (Ratarstvo i Povrtarstvo)
The study investigated the cultivation, chemical composition, and potential applications of Salvia officinalis L. cultivar "Primorska" over three years. The research revealed that the essential oil of S. officinalis contains significant amounts of oxygenated monoterpenes, including a-thujone (19.9-29.0%), camphor (15.8-19.6%), b-thujone (12.3-13.3%), and 1,8-cineole (8.8-11.3%). The content of these compounds varied across years and correlated with temperature fluctuations. The hydrolate derived from S. officinalis exhibited a similar chemical profile to the essential oil, with camphor emerging as the most abundant compound (42.4-49.6%). Statistical analysis revealed correlations between temperature, precipitation, and the content of various compounds in both the essential oil and hydrolate. Temperatures are in strong negative correlation with a-thujone (KT=-36.500), and in positive correlation with camphor (KT=9.5), b-thujone (KT=4.500) and 1,8-cineole (KT=5.000) in essential oil. In hydrolates is also noted similar trend of correlations: negative correlations between temperature and a-thujone (KT=-32.000), and positive correlations temperature and camphor (KT=34.000), b-thujone (KT=7.000), and 1,8-cineole (KT=7.000). S. officinalis essential oil is highly valued in the food and pharmaceutical industry, as well as in cosmetics, perfumery and aromatherapy. Numerous studies have indicated its antioxidant, antimicrobial, anti-inflammatory and anticancer potential. The study also highlighted potential applications of S. officinalis hydrolate in cosmetics, food sanitation, and pharmaceuticals due to its antioxidant properties and moderate antimicrobial effects. Overall, the research contributes to a deeper understanding of S. officinalis products' chemical composition and underscores the potential of its hydrolate as a valuable resource in multiple industries. Further exploration into its applications and benefits will drive innovation in product development and utilization.